DAMPAK MEDIA SOSIAL TERHADAP POLA INTERAKSI SOSIAL BUDAYA SISWA DI SD NEGERI 05 PEMULUTAN - Winda Agustin; Rodiatun Niswah; Rini Apriyani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The main purpose of this study was to determine the impact of social media on socio-cultural interaction patterns in students at SD Negeri 05 Pemulutan. The research method used is descriptive qualitative through observation, interviews, and observations. The results highlight the significant impact of social media use on the socio-cultural interaction patterns of students at SD Negeri 05 Pemulutan. The findings showed that students who actively used social media tended to have less direct social interaction with their peers at school. They are more inclined to engage in online interactions through text messaging, social networking platforms, or instant messaging apps.